Iterative Learning Impedance Control based on Physical Recovery Condition Elevation of Impaired Limb - Jinbao He; Xia Zhuge; Zaifei Luo; Guojun Li; Zhang Yinchun (Institute of Advanced Engineering and Science, 2014)
Rehabilitation robots have been designed to improve the daily life activity ability of patients with impaired limb. In this paper, we proposed a new iterative learning impedance control(ITLC) algorithm, which based on the physical recovery condition of impaired limb. Firstly, we evaluated the physical recovery condition elevation of impaired limb with periodic force parameter and trajectory tracking ratio(TTR) parameter, and modified the desired impedance on line using fuzzy method according to the change of physical recovery condition. Secondly, we designed an adaptive impedance controller that can be modified using iterative learning method. The convergence was analyzed based upon the Lyapunovlike positive definite sequence, which was monotonically decreasing under the proposed control schemes. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3867